Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) dengan Metode Pemecahan Masalah (Problem Solving) Terhadap Hasil Belajar Matematika Siswa SMP-IT Darul Muhsin Nahdlatul Wathan Tahun Pembelajaran 2020/2021 - Baiq Dwi Ernawati; Baidowi Baidowi; Muhammad Turmuzi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the effect of the Numbered heads Together (NHT) cooperative learning model with the problem-solving method on the learning outcomes of SMP-IT Darul Muhsin Nahdlatul Wathan academic year 2020/2021. In determining the sampling technique with saturate sampling type, where the samples in this study were students of class VIII-A as the control class and students of class VII-B as the experimental class. The instrument used in this study was an observation sheet and a test of student learning outcomes (posttest) on the function relation material. Quantitative analysis was carried out using the t-test, the value of count bigger table so that H0 was rejected. The results showed that the application of Numbered heads Together (NHT) cooperative model with the problem solving method had an effect on student learning material for class VIII SMP-IT Darul Muhsin Nahdlatul Wathan for the 2020/2021 academic year.